Surface characterization of oxide films formed on aluminium alloy with the incorporation of functionalized carbon nanotube - Yaakob, Yazid; Mamat @ Mat Nazir, Md Shuhazlly; Mohd Zaid, Mohd Hafiz; A. Aziz, Aflah; Muktar, Muhammad Izzat; Chan, Kar Fei; Liza, Shahira (Malaysian Tribology Society (Mytribos), 2024)
Aluminium oxide film incorporated with functionalized CNTs were fabricated by an anodizing method using 20% diluted sulphuric acid. This study aims to examine the influence of different acid molarity during the CNTs functionalization toward the surface characterization of aluminium oxide composite film. The functional group that is attached at the surface of CNTs were analyzed using FTIR while the surface properties were analyzed using xray diffraction (XRD), scanning electron microscopy (SEM), 3D optical profiler and Vickers microhardness tester. FTIR result shows that the presence of hydroxyl group at 1650cm-1 proves that the CNTs were successfully functionalized. The results obtained from the SEM analysis indicate that the incorporation of functionalized CNTs contributes to a reduction in the porosity of the composite film by 72%. The result of 3D profiler revealed that the functionalized CNTs in the composite film reduce the average surface roughness to 65%. Besides that, the microhardness was enhanced by 94%.